Improving Oral Production Through Interactions in a Task-Based Approach (2023)
ABSTRACT : This action research aimed at establishing the impact of Task-Based-Learning to foster class interactions and improve oral production. It was conducted in a public school in La Ceja, Antioquia with 47 sixth graders. Action strategies included the three-step cycle of TBL to measure students’ prior knowledge and needs. The requirements of the Task, to build and share the Task and, to give the Feedback of the Task were applied. Data gathering instruments included teacher’s journal, students’ artifacts, and a focus group. Findings referred to interactions in English, interactions to support each other, improving oral production, the use of patterns as support for oral production, and the use of prior vocabulary to oral participation in class.